Correlation between carbohydrate intake and dental caries in obese individuals - Ignatius Setiawan; Ananda Sagita; Ibnu Suryatmojo; Dewi Marhaeni Diah Herawati; Irna Sufiawati; Sunardhi Widyaputra (Dental Journal (Majalah Kedokteran Gigi), 2021)
Background: Nowadays, obesity is one of the biggest public health problems. Obesity is an excessive accumulation of fat that can occur when fat-producing foods, such as carbohydrates or sugar, are over-consumed. Sucrose is a type of carbohydrate contained in food and is a medium for bacterial growth. Therefore, the consumption of sucrose can increase the risk of dental caries. Purpose: This study aims to analyse the correlation between carbohydrate intake and dental caries in obese individuals. Methods: This study was an observational analytic study with a cross-sectional design. In this study, 50 participants aged 18–40 were selected from an obese community in Jakarta using a quota sampling technique. The carbohydrate intake was assessed using the food frequency questionnaire (FFQ), the body fat percentage was measured with the bioelectrical impedance analysis method, and the dental caries index was assessed using the decayed, missing and filled teeth (DMF-T) index. The data obtained were tested with a simple linear regression statistical test at a significance level of 5%. Results: The results showed that the average carbohydrate daily intake value of obese individuals was 1209.84 g, while the average value of the DMF-T index for obese individuals was 7.98. The results of the statistical tests revealed that there was a strong and positive correlation between carbohydrate intake and the DMF-T index. The effect of carbohydrate intake on the DMF-T index was 50.98%. Conclusion: A positive correlation means that the larger the carbohydrate intake, the higher the DMF-T index. Hence, controlling carbohydrate intake can prevent dental caries.